Pemasaran Politik dalam Media Sosial (Studi Political Marketing Pilkada Serdang Bedagai 2020 melalui Facebook) - Nurhajija Khofifa Br Munthe; Dini Arti Lubis; Marzuki (Hijaz: Jurnal Ilmu-Ilmu Keislaman, 2022)
Digital democracy is a term that has always been used in the political sphere. Internet media has become a lot of forums for political actors, especially in conducting political campaigns. The development of the digital age that is increasingly advanced makes political campaigns through social media, especially Facebook, more intensively carried out. This social media can attract many voices considering the potential of the Indonesian people who are still very many users. So that Facebook is one of the media that can be used as a means of promoting political campaigns. The purpose of this study is to determine political marketing in siosial media (political marketing study of the 2020 Serdang Bedagai regional election through Facebook). The results showed that political marketing on social media in the 2020 Serdang Bedagai regional election through Facebook was quite effective. This was achieved because of the ability of political marketing activities carried out, namely by utilizing social media after making visits.